9 things successful people do differently /Heidi Grant Halvorson. - Halvorson, Heidi Grant-,1973-
Are you at the top of your game--or still trying to get there? Take your cues from the short, powerful 9 Things Successful People Do Differently, where the strategies and goals of the world's most successful people are on display--backed by research that shows exactly what has the biggest impact on performance. Here's a hint: accomplished people reach their goals because of what they do, not just who they are. Readers have called this "a gem of a book." Get ready to accomplish your goals at last.